2014
DOI: 10.2134/ats-2013-0101-rs
|View full text |Cite
|
Sign up to set email alerts
|

Cultivar Performance of Low-Input Turfgrass Species for the North Central United States

Abstract: Turfgrass managers are in need of low‐input turfgrass species options. We have previously identified a number of species that do well as low‐input, sustainable turf in the north central United States. The objective of this study was to evaluate multiple cultivars of turfgrass species with known adaption to low‐input environments in the North Central Region. Twenty‐five turfgrass cultivars and selections, representing ten grass species, were evaluated at eight locations. Plots were established in late summer 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
27
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 15 publications
(26 reference statements)
3
27
0
Order By: Relevance
“…In the past decades, turfgrass breeders have developed turfgrasses that exhibit low‐input characteristics such as drought tolerance and reduced nitrogen requirements (Johnson ; Bonos and Huff ; Watkins et al ). Meanwhile, progress has been made to identify native North American species with low‐input characteristics (Watkins et al ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the past decades, turfgrass breeders have developed turfgrasses that exhibit low‐input characteristics such as drought tolerance and reduced nitrogen requirements (Johnson ; Bonos and Huff ; Watkins et al ). Meanwhile, progress has been made to identify native North American species with low‐input characteristics (Watkins et al ).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Mintenko et al () showed that several grass species native to North America, such as tufted hairgrass ( Deschampsia cespitosa ) and prairie junegrass ( Koeleria macrantha ), are suitable for low‐maintenance turfgrass use in the Northern Great Plains region. Diesburg et al () and Watkins et al (, ) suggested that species such as tall fescue ( Schedonorus arundinaceus ), hard fescue ( Festuca trachyphylla ), sheep fescue ( Festuca ovina L . ), and colonial bentgrass ( Agrostis capillaris L .)…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To fulfill the needs of consumers and to contribute to environmental sustainability, turfgrass breeding programs evaluate, develop, and introduce turfgrasses with superior traits. Previously, various turfgrass species have been assessed for pest and disease resistance (Bonos et al, 2006;Cisar, 2010;Watkins et al, 2014), climatic region adaptation (Mintenko et al, 2002), drought tolerance, and reduced nitrogen requirements (Bonos and Huff, 2013;Johnson, 2008;Watkins et al, 2014). A previous study (Yue et al, 2012) investigated priorities for North American rosaceous crop breeding programs and found that breeders regarded the two ends of the supply chain (producer/ growers and the consumers) as the most important parties when setting trait priorities.…”
mentioning
confidence: 99%
“…For instance, perennial ryegrass generally has better quality at lower mowing heights (3.8 cm compared with 5.0 or 6.3 cm); this increased level of maintenance also results in higher weed pressure than when the grass is maintained at higher heights of cut . Kentucky bluegrass typically requires high input levels for maintaining adequate quality (DeBels et al, 2012), and may not perform as well as other species when inputs are limited (Watkins et al, 2014). Turfgrass breeders have worked to improve these species for use in lower-input situations (Bonos and Huff, 2013), but the use of alternative species is another promising approach.…”
mentioning
confidence: 99%